Hydrogen storage studies of nanoparticulate AI and TiMn based compounds - Murshidi, Julie Andrianny (Curtin University, 2012)
Concerns about the impact that fossil fuels have on the environment and their increasing price to the consumer have led to research being undertaken to evaluate and refine other energy carriers that will be comparable to fossil fuels. Significant interest has been associated with hydrogen. Hydrogen is widely known as a promising energy carrier for the transportation sector. However at present no known material or storage means exists that satisfies all requirements to enable high-volume automotive application. Transition to using hydrogen storage technology in vehicles might first include its implementation in specialty vehicles, portable power supply and stationary power supply. Due to this fact, research into materials based hydrogen storage has grown significantly over the past decade. Of the wide variety of materials based hydrogen storage, three different materials were chosen as the primary focus of this project; (1) Aluminium nanoparticles, (2) AlH3 nanoparticles and (3) TiMn alloy.Al nanoparticles were synthesised by mechanochemical reactions of AlCl3 + 3Li → Al + 3LiCl using different LiCl:Al volume ratios (6.786:1 , 9.665:1 and 12.544:1). LiCl was used as the buffer. Sample synthesised without the addition of buffer led to the formation of Al nanoparticles with an average particle size of 50 nm. Addition of sufficient quantity of buffer resulted in the formation of Al with average particle sizes down to 13 nm. The addition of LiCl as a buffer helps to separate the synthesized Al particles, essentially restricting particle growth and promoting nanoparticle formation. Attempted hydrogenation of Al nanoparticles (13 nm) using a mixed H2/scCO2 media showed no H2 absorption. This indicates that an Al particle size less than (13 nm) is required to introduce hydrogen into pure Al at pressure and temperature attempt herein (73.8 bar and 31.1C). Furthermore the presence of oxide layer (Al2O3) on Al nanoparticles during scCO2/H2 reaction limited the rate of hydrogen permeation on Al nanoparticles.AlH3 nanoparticles were synthesised by mechanochemical reactions of the 3LiAlH4 + AlCl3 using different LiCl:AlH3 volume ratios (0.76:1, 2:1, 5:1 and 10:1) at 77 K. The addition of LiCl as a buffer leads to the reduction of the synthesized AlH3 crystallite size, restricting AlH3 decomposition and preventing high Al yields. Quantitative Rietveld results coupled with hydrogen desorption measurements suggest the presence of an amorphous AlH3 phase in mechanochemically synthesized samples. TEM results show that the synthesized AlH3 comprised of 10 - 30 nm particle size range. For hydrogen desorption measurements, it is clear that AlH3 particle size reduction when ball milling using buffer does effectively increase the H desorption rate compared to the case without using buffer. For hydrogen absorption measurements, decomposed AlH3 nanoparticles with 10 - 30 nm in size underwent pressures of 280 bar at -196 C, 1420 bar at 25C, 1532 bar at 50°C, 1734 bar at 100°C and 1967 bar at 150°C with no hydrogen absorption was detected.Ti-Mn alloy compounds with the composition TiMn2, Ti0.97Zr0.019Mn1.5Cr0.57 and Ti0.7875Zr0.2625Mn0.8Cr1.2 were synthesised and compared to the commercially available Ti0.97Zr0.019V0.439Fe0.097Cr0.045Al0.026Mn1.5 alloy composition. An amorphous Ti-Mn alloy was formed when the starting reagents were mechanical alloying for 40 h. The corresponding crystalline phase TiMn was formed when the amorphous alloy was annealed at 800C. The addition of a process control agent (Toluene) leads to the formation of a carbide phase (TiC) in the samples. The presence of impurities, carbide (TiC) and oxide (TiO) phases resulted a decrease in C14 laves phase wt.% in the synthesised samples. Only 37.24, 31.5 and 32.81 wt.% C14 phase was formed in TiMn2, Ti0.97Zr0.019Mn1.5Cr0.57 and Ti0.7875Zr0.2625Mn0.8Cr1.2 respectively. The result also showed that the theoretical value of 1.9 hydrogen wt.% could not be reached by these samples.